"Because she was my first girlfriend, I didn't know any different": Making the case for mainstreaming same‐sex sex/relationship education - Donovan, Catherine; Hester, Marianne (Sex Education, 2008)
In this paper we present the case for those entering/considering same-sex relationships to be included in sex and relationship education in schools. The Government's Guidance on Sex and Relationship Education provides a rationale for including same-sex relationships when it says that schools should meet the needs of all their pupils "whatever their developing sexuality." Research on sex education and domestic violence prevention for schools has highlighted issues of gender, power, the importance of understanding context in providing skills and knowledge for safer sex and non-abusive relationships. However, both tend to assume the context is heterosexuality. Results from our Economic & Social Research Council-funded study of domestic violence in same-sex and heterosexual relationships indicates that those aged under 25 years of age and those in first same-sex relationships are particularly vulnerable to experiencing domestic violence. Four themes arise from the qualitative data that provide a rationale for the provision of sex and relationship education to these young people: first same-sex relationships as an affirmation of identity; and lack of knowledge about what to expect in same-sex relationships; of embeddedness in lesbian, gay, bisexual, transgender and queer friendship networks; and of resources to seek help.
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; LGBTQIA2+; approches et analyses; discours dominant; genre; hétérosexisme; identités LGBTQIA2+; inégalités; périodes historiques; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; violences; violences conjugales; éducation sexuelle; étude qualitative

Le siècle dans la tourmente du féminisme - Daigle, Johanne (Globe : revue internationale d’études québécoises, 2000)
L’empreinte du féminisme sur le XXe siècle québécois est indélébile. De l’aube au crépuscule du siècle, la « question des femmes » a coloré les grands débats, imprégné les luttes socio-politiques et laissé sa marque sur les systèmes de lois, les institutions, l’organisation du travail et les modes de vie. Cet article veut montrer comment, dans une perspective historique, la « question des femmes » — ainsi posée par les élites masculines — fut pressentie comme l’une des grandes interrogations de ce siècle et comment les changements survenus dans la reconfiguration des rapports entre hommes et femmes — des identités sexuelles aux modèles qui les supportent — restent au coeur des enjeux d’une société.
https://www.erudit.org/en/journals/globe/2000-v3-n2-globe1497493/1000582ar/
Keywords: 1900-1999; EDI; amériques; approches et analyses; conflit; cours; discipline; discours dominant; droits des femmes*; fem1000; histoire; histoire et politique; inégalités; militance; patriarcat; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail; épistémologie